Nos Campos de Cima da Serra: ser preto, pardo e branco na Vila de Lages, 1776-1850 - Vicenzi, Renilda (Universidade do Vale do Rio dos Sinos, 2015)
Analyzing the dynamics of space occupation of Lages village, situated on the way of troops between the fields of Curitiba and Viamão, in the late eighteenth and early nineteenth century, constitutes a central objective of this work. Therefore, through the trajectories of individuals from different backgrounds and color, we analyze the agrarian and social formation of these places. On farms of Lages fields, besides breeding (vacuns, horsy and mules) for marketing starting in Sorocaba (SP) markets followed by Desterro (SC), there was the agricultural production of food for internal expenses in the properties, and the meager excess were sold in small urban center of the village. In the properties (farms and ranches), lived side by side free and captive men. In general, the owners of sites and farms had their labor formed by the nuclear family, and occasionally had the presence of aggregates and one or two captives. On the other hand, the lords of farms were living with their families, captives and aggregates. Being landowner and captives was not exclusive to whites; browns and blacks also were.
Keywords: Vila de Lages; Homens de cor; Escravos e livres; Produção agrícola e pecuária; Lages Village; Color man; Slaves and free; Agricultural and livestock production; ACCNPQ::Ciências Humanas::História